2012
DOI: 10.1021/ja3090498
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Chaetoviridin and Chaetomugilin Gene Cluster in Chaetomium globosum Reveal Dual Functions of an Iterative Highly-Reducing Polyketide Synthase

Abstract: We report the identification and characterization of the caz biosynthetic cluster from C. globosum and the characterization of a highly-reducing polyketide synthase (PKS) that acts in both a sequential and convergent manner with a nonreducing PKS to form the chaetomugilin and chaetoviridin azaphilones. Genetic inactivation studies verified the involvement of individual caz genes in the biosynthesis of the azaphilones. Through in vitro reconstitution, we demonstrated the in vitro synthesis of chaetoviridin A 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
123
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 28 publications
1
123
0
Order By: Relevance
“…This information was supported by the HMBC correlations from H[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and from H-8 to C-23, as well as the 1 H− 1 H COSY spin system of H 2 -20/H 2 -21/H 2 -22.…”
mentioning
confidence: 88%
“…This information was supported by the HMBC correlations from H[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and from H-8 to C-23, as well as the 1 H− 1 H COSY spin system of H 2 -20/H 2 -21/H 2 -22.…”
mentioning
confidence: 88%
“…We chose to integrate cghA into the chaetoviridin biosynthetic PKS gene cazM [20] so that the integration event would be indicated by the loss of formation of chaetoviridin A 8 and B 9 . [19] A control experiment verified that disruption of cazM would not affect the production of 1 (Figure 4, i vs. ii).…”
mentioning
confidence: 99%
“…The resulting yeast strain containing the desired plasmid was then used directly to elucidate the product of the iPKSs through expression of the encoded enzymes and analysis of the resulting products (Mao et al, 2015). Other examples of TAR-based assembly of iPKSs include cazF and cazM from the chaetoviridin biosynthetic gene cluster in Chaetomium globosum (Winter et al, 2015; Winter et al, 2012a); bref-PKS from the biosynthetic gene cluster of brefeldin A in Eupenicillium brefeldianum (Zabala et al, 2014); and fma-PKS from the biosynthetic gene cluster of fumagillin in Aspergillus fumigatus (Lin et al, 2013). A variation of this strategy is to first assemble the entire iPKSs gene using overlap extension PCR (OE-PCR), followed by transformation into yeast along with the vector to yield the intact expression plasmid via recombination.…”
Section: The S Cerevisiae Toolbox For Cloning and Enzyme Reconstimentioning
confidence: 99%
“…Native producers often evolve their own solutions to protect themselves from the presence of toxic compounds, such as specific transporter proteins or other enzymes that confer self-resistance to the native host (Martín et al, 2005). These self-resistance mechanisms can take the form of product-specific transporters like the putative transporter cazK from Chaetomium globosum and the putative efflux pump lovI from A. terreus (Kennedy et al, 1999; Winter et al, 2012b). Recently, Ley et al showed that integration of the putative efflux pump mlcE , from the compactin PKS cluster of P. citrinum, into the S. cerevisiae genome conferred increased resistance to mevastatin, lovastatin, and simvastatin, as compared to the wild type strain.…”
Section: Engineering Production Of Fungal Pkss and Polyketides In mentioning
confidence: 99%